DATA ENGINEERING IN CRISP-DM PROCESS PRODUCTION DATA – CASE STUDY - BRZOZOWSKA, Jolanta; PIZOŃ, Jakub; BAYTIKENOVA, Gulzhan; GOLA, Arkadiusz; ZAKIMOVA, Alfiya; PIOTROWSKA, Katarzyna (Applied Computer Science, 2023)
The paper describes one of the methods of data acquisition in data mining models used to support decision-making. The study presents the possibilities of data collection using the phases of the CRISP-DM model for an organization and presents the possibility of adapting the model for analysis and management in the decisionmaking process. The first three phases of implementing the CRISP-DM model are described using data from an enterprise with small batch production as an example. The paper presents the CRISP-DM based model for data mining in the process of predicting assembly cycle time. The developed solution has been evaluated using real industrial data and will be a part of methodology that allows to estimate the assembly time of a finished product at the quotation stage, i.e., without the detailed technology of the product being known.